The influence of environmental knowledge on green supply chain management in achieving business performance and sustainability performance of culinary MSMEs in Indonesia - Nurul Hidayati; Agung Nugraha; Nur Hadi Wijaya; Heti Mulyati (Education and Development Research, 2026)
This study aimed to examine the impact of environmental knowledge (EK) and green supply chain management (GSCM) on business performance (BP) and sustainability performance (SP) in the context of MSMEs in the culinary sector in Bogor City, Indonesia. In the context of culinary MSMEs in Bogor City, research addressing the integration of EK–GSCM–BP–SP and the mediating effect of GSCM is still scarce, particularly within this specific sector and regional setting. The research was conducted over six months, with the research location being in Bogor City in February-July 2025. This study employed a multistage sampling method with cluster sampling and purposive sampling. Data was collected from 210 MSME practitioners and analyzed using Structural Equation Modeling – Partial Least Square (SEM-PLS) with SmartPLS 4. This sample number was an appropriate sample size for the application of SEM-PLS analysis. The results of the study show that EK has a positive and significant effect on GSCM, BP, and SP. The study also indicates that GSCM positively and significantly affects BP and SP, and BP also positively and significantly influences SP. Furthermore, GSCM was found to positively and significantly mediate the relationship between BP and SP. The implementation of GSCM among MSMEs can be improved through capacity-building efforts such as training, mentoring, and collaboration with suppliers and green communities, supported by government policies, incentives, continuous education, and enabling facilities.